2017
DOI: 10.1371/journal.pone.0189990
|View full text |Cite
|
Sign up to set email alerts
|

Somatic instability of the expanded GAA repeats in Friedreich’s ataxia

Abstract: Friedreich’s ataxia (FRDA) is a genetic neurodegenerative disorder caused by transcriptional silencing of the frataxin gene (FXN) due to expansions of GAA repeats in intron 1. FRDA manifests with multiple symptoms, which may include ataxia, cardiomyopathy and diabetes mellitus. Expanded GAA tracts are genetically unstable, exhibiting both expansions and contractions. GAA length correlates with severity of FRDA symptoms and inversely with age of onset. Thus, tissue-specific somatic instability of long GAA repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…These ndings contradict the established correlation between GAA repeat length and disease milestones and suggest that these associations may be valid only when neurological symptoms are considered. Interestingly, cumulative evidence showed that GAA repeat expansions are subjected to somatic instability with accumulation of further contractions/expansions, which can lead to marked differences in the affected tissue and possibly explain lack of correlation between the course non-neurological symptoms and GAA1-repeat length (27). Eventually, we cannot exclude that the smaller number cases in the siblings´ group and in group with non-neurological onset contributed to the lack of signi cant correlation between age at onset and GAA1-repeat length.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings contradict the established correlation between GAA repeat length and disease milestones and suggest that these associations may be valid only when neurological symptoms are considered. Interestingly, cumulative evidence showed that GAA repeat expansions are subjected to somatic instability with accumulation of further contractions/expansions, which can lead to marked differences in the affected tissue and possibly explain lack of correlation between the course non-neurological symptoms and GAA1-repeat length (27). Eventually, we cannot exclude that the smaller number cases in the siblings´ group and in group with non-neurological onset contributed to the lack of signi cant correlation between age at onset and GAA1-repeat length.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathogenesis remains unclear. However, tissue specific somatic repeat instability and selective tissue vulnerability likely contribute to the characteristic selective dysfunction of the central and peripheral nervous systems, heart, and pancreas . The predominant pathological involvement in the PNS occurs at the dorsal root ganglion resulting in a sensory neuronopathy .…”
Section: Discussionmentioning
confidence: 99%
“…FRDA is a (GAAGAA-GAA)n repeat expansion disorder in intron 1 of the frataxin gene on the positive strand of chromosome 9q21.11 leading to epigenetic changes within the frataxin gene, culminating in heterochromatin-mediated transcriptional silencing of the gene [25]. However, genetic modifiers may also account for the somatic instability of the expanded (GAA)n that drives disease progression [28]. Patients may also suffer from cardiomyopathy, optic neuropathy, skeletal deformity and diabetes mellitus.…”
Section: Autosomal Recessive Cerebellar Ataxiamentioning
confidence: 99%
“…As in SCA, age at onset and progression of FRDA partly depends on the TNR repeat length [27]. However, genetic modifiers may also account for the somatic instability of the expanded (GAA)n that drives disease progression [28].…”
Section: Autosomal Recessive Cerebellar Ataxiamentioning
confidence: 99%